The Impact of Training and Compensation on Employee Performance: The Moderating Role of Human Resource Quality - Raden Fatchul Hilal; Djoko Widagdo (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: The quality of human resources (HR) is a key determinant of organizational success, especially in structured work environments.Purpose: This study endeavored to ascertain the efficacy of performance-based training and compensation as a means of enhancing the quality of the human resources of the company. Design/Methodology/Approach: A quantitative survey was conducted on 60 employees of the Aviation Security Company in Yogyakarta, selected using simple random sampling. Data were collected through a closed-ended questionnaire and analyzed using PLS-SEM. Result: The analysis yielded results that indicated a significant impact of training on employee performance at the Yogyakarta branch of the Aviation Security company. Furthermore, the findings suggest a direct impact of compensation on employee performance within the same context.Conclusion: The findings of this study indicate a direct effect of training and compensation on employee performance at the Yogyakarta branch of the Aviation Security company. While HR quality also contributes to performance outcomes, the study did not find sufficient evidence to support its role as a moderating variable. These results suggest that training and compensation remain central components in enhancing employee performance, regardless of variations in HR quality levels.Originality/Value (State of the art): This study introduces an integrated HRM model and reveals that HR quality, while impactful, does not moderate training or compensation effects within structured work systems. Keywords: training, compensation, employee performance, human resources quality, aviation security